Impact of increasing methyl branches in aromatic hydrocarbons on diesel engine combustion and emissions. (15th March 2018) - Talibi, Midhat; Hellier, Paul; Ladommatos, Nicos
Highlights: Series of alkylbenzenes with varying number of methyl branches were tested. An oxygenated aromatic, benzaldehyde was also tested for comparison. Ignition delay increased with number of methyl branches due to OH∗ consumption. Exhaust CO and THC emissions increased above 30% aromatic proportion. Number of particles increased with increasing number of methyl branches. Abstract: Lignocellulosic materials have been identified as potential carbon–neutral sources of sustainable power production. Catalytic conversion of lignocellulosic biomass results in liquid fuels with a variety of aromatic molecules. This paper investigates the combustion characteristics and exhaust emissions of a series of alkylbenzenes, of varying number of methyl branches on the monocyclic aromatic ring, when combusted in a direct injection, single cylinder, compression-ignition engine. In addition, benzaldehyde (an aldehyde (-CHO) branch on the monocyclic ring) was also tested. All the molecules were blended with heptane in different proportions, up to 60% wt/wt. The tests were conducted at a constant engine speed of 1200 rpm, a fixed engine load 4 bar IMEP, and at two injection modes: constant start of fuel injection at 10 CAD BTDC, and varying fuel injection timing to maintain constant start of fuel combustion at TDC. The results showed that the ignition delay period increased with increasing number of methyl branches on the ring, due to the rapid consumption of OH radicals by the alkylbenzenes for oxidation to stable benzyl radicals. Peak heat release rates, and concurrently NOx emissions, initially increased with increasing methyl branches, but subsequently both decreased as the bulk of heat release occurred further into the expansion stroke with significant thermal energy losses. With the exception of toluene, the number of particles in the engine exhaust increased as the number of methyl branches on the aromatic ring increased, attributable to the formation of thermally stable benzyl radicals.